The Concept of Profit Sharing on Deposits Sharia in Islamic Bank for Non-Muslim Market - Moh Farih Fahmi; Binti Mutafarida; Ahmad Hanif Fajrin (Universitas Muhammadiyah Surabaya, 2022)
A concept of an ideal alternative solution to Islamic banking that is less attractive, especially in sharia deposit fund investment products, is certainly an issue that must be resolved immediately. The concept of Islamic banks that should be oriented towards rahmatan lil alamin certainly must be open to all humanity, including non-Muslims. The customers' insecurity towards sharia bank deposit products is one of the reasons for this is